Hidden Homelessness: A Scoping Review and Avenues for Further Inquiry. Issue 2 (21st April 2023) - Deleu, Harm; Schrooten, Mieke; Hermans, Koen
Abstract : Traditional interpretations of homelessness focus on people living on the streets or in shelters. However, homelessness encompasses many more living situations. This article reports on a scoping review of studies on hidden homelessness. A systematic search in scientific databanks was combined with an exploration of Google Scholar. The results of the review reveal a lack of consensus regarding the definition of the concept. Moreover, since most studies focus on a certain subgroup in the population, it is hard to compare profile characteristics of people living in different forms of homelessness. The applied research methods prove to be valuable, although they often underestimate the number and/or character of the phenomena. Very little longitudinal research on hidden homelessness seems to be available. Based on the findings of the scoping review, the article draws up an agenda for further research in order to capture the complex reality of contemporary forms of homelessness.